Prediksi Penambahan Charging Port Untuk Bus Listrik Transjakarta Menggunakan Algoritma Decision Tree - Romadhon, Raihansa; Aldisa, Rima Tamara (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Transjakarta bus is one of the public transportation options used in cities with dense populations and severe congestion, aiming to facilitate mobility. This research focuses on the implementation of the Decision Tree algorithm to predict the movement of Transjakarta electric buses and determine the optimal placement of charging ports in each corridor. Based on the evaluation results, corridors 1, 4, 5, 6, 7, 11, 13, and 14 do not require additional charging facilities because the remaining battery capacity of the buses at the end of the journey is still above 30%. Conversely, corridors 2, 8, 9, 12, 3, and 10 need to be equipped with charging ports, especially for BYD K-9 and SKYWELL buses, considering the higher battery consumption of these buses, thus requiring additional charging before completing the route. The evaluation of the model's performance shows significant accuracy, with evaluation metrics such as precision, recall, and F1-score with a value of 100%, indicating adequate results for field implementation. This research contributes significantly to the field of public transportation, especially in the management of environmentally friendly electric buses.